Effect of dihydroartemisin-piperaquine for malaria intermittent preventive treatment on dolutegravir exposure in pregnant women living with HIV - Banda, Clifford (Department of Medicine, 2023)
Background: In sub-Saharan Africa, the disease burden of malaria and HIV infections overlap. In settings with moderate-to-high malaria transmission intensity, pregnant women living with HIV (PWLHIV) require both antiretroviral therapy and malaria intermittent preventive treatment (IPTp). Dihydroartemisinin-piperaquine has been identified as a promising alternative to sulfadoxine-pyrimethamine for malaria prevention in pregnancy. However, another antimalarial drug, artesunate-amodiaquine, similar to dihydroartemisininpiperaquine, was previously shown to reduce dolutegravir exposure in non-pregnant adults. Objective: To investigate the effect of dihydroartemisinin-piperaquine for IPTp on dolutegravir plasma exposure in pregnant women on dolutegravir-based antiretroviral therapy. Methods: We conducted an open-label, non-randomised, fixed sequence, pharmacokinetic study in PWLHIV in Malawi. Dolutegravir concentrations were measured over a 24-hour period, before and after the recommended three-day treatment dose of dihydroartemisininpiperaquine in 12 pregnant women in their 2nd or 3rd trimester. Non-compartmental analysis was performed, and geometric mean ratios (GMRs) and 90% confidence intervals (CIs) were generated to compare dolutegravir pharmacokinetic parameters between the two treatment periods. Results: Co-administration of dihydroartemisinin-piperaquine and dolutegravir increased dolutegravir's overall exposure (AUC0-24hr) and maximum concentration (Cmax) by 30% (GMR,1.30; 90% CI, 1.11-1.52) and 31% (GMR, 1.31; 90% CI,1.13-1.51), respectively. Furthermore, dolutegravir's trough (C24) concentration increased by 42% (GMR,1.42; 90% CI,1.09-1.85). The combined treatments were well tolerated with no serious adverse events observed. Conclusion: Dihydroartemisinin-piperaquine may be administered as IPTp with dolutegravir-based antiretroviral therapy in pregnant women as the modest increase in dolutegravir exposure, similar to pharmacokinetic parameter values published previously, assures its efficacy without any clinically significant adverse events observed in this small study